Analisis Faktor Yang Mempengaruhi Produk Domestik Regional Bruto Di Provinsi Jawa Barat Tahun 2015-2019 - Suci Agustina; Syamsul Hadi (Jurnal Ilmu Ekonomi, 2021)
This study aims to determine the effect of Regional Original Income, Manpower, Domestic Investment, and General Allocation Funds on the Gross Regional Domestic Product of Regencies/Cities in West Java Province for 2015-2019. The researcher used a sampling technique with the Non-Regency Method in this study. Probability Sampling using Purposive Sampling, totaling 18 districts and nine cities. This study uses panel data. In this study, the fixed effect method is the best model. The results of this study are Regional Original Income and General Allocation Funds have a positive effect on the Gross Regional Domestic Product of districts/cities in West Java Province. In contrast, Domestic Workforce and Investment have a negative and significant impact on the Gross Regional Domestic Product of Regencies/Cities in West Java Province.